Pharmacognostical and physico-chemical evaluations of Cardiospermum halicacabum L. seeds - B. Mohaddesi; A. dudhrejiya; M. Chauhan (Iranian Society of Pharmacognosy, 2016)
Background and objectives: Cardiospermum halicacabum L. is a climber plant of Sapindaceae family with certain medicinal properties that have made it to be used traditionally in different systems of medicine such as Ayurveda, Homeopathy and Unani medicine. Literature survey has revealed the reports about some investigations but references were not available about the seeds of C. halicacabum; hence, the seeds were selected for the present investigation. Methods: Detailed macroscopic and microscopic studies of C. halicacabum seeds and powder were carried out, physico-chemical parameters, preliminary and quantitative phytochemical analyses of different extracts of the seeds performed. Besides, the amount of total phenols and flavonoids in different extracts were determined. Results: The phytochemical screening gave a positive test for presence of various phytoconstituents like alkaloids, flavanoids, and tannins. The amount of total phenols was found to be between 29.697±0.232 to 187.372±0.615 mg pyrogallol equivalent/g and the content of flavonoids between 27.833±0.412 to 139.261±0.412 mg quercetin equivalent/g in various extracts.   Conclusion: The present work has reported the detailed macroscopic, microscopic and physio-chemical evaluations of the seeds of C. halicacabum and provided information which would be helpful for better identification and standardization of C. halicacabum seeds.